Karyotype and idiogram of the axis deer (Axia axis, Cervidae) by conventional staining, GTG-, high-resolution GTG-, and Ag-NOR-banding techniques - Hathaipat Khongcharoensuk (2018)
© 2017 The Japan Mendel Society. The standardized karyotype and idiogram of the axis deer (Axis axis, Cervidae) at Khon Kaen Zoo, Thailand were established. Blood samples were taken from two male and two female axis deer. After standard whole blood T-lymphocytes were cultured at 37°C for 72 h in the presence of colchicine, metaphase spreads were performed on microscopic slides and air-dried. Conventional staining, GTG-, Ag-NOR-banding and high-resolution techniques were applied to stain the chromosome. The results showed that the diploid chromosome number of A. axis was 2n=66 and the fundamental number (NF) was 70 in both male and female. The types of autosomes observed were 2 large metacentric, 2 large submetacentric, 2 large telocentric, 6 medium telocentric and 52 small telocentric chromosomes. The X chromosome was a large telocentric chromosome, and the Y chromosome was a small telocentric chromosome. The GTG-banding and high-resolution techniques provided that the respective numbers of bands and locations of A. axis were 246 and 294, and each chromosome pair could be clearly differentiated. In addition, the subtelomeric q-arm of chromosome pair 2 and the telomeric q-arm of chromosome pair 4 showed clearly observable nucleolar organizer regions (NORs) and secondary constrictions. Our results are the first reports of GTG-, high-resolution GTG- and Ag-NOR-banding techniques on this species. The karyotype formula of A. axis is as follows: {equation presented}